Działalność kinematograficzna i rekolekcyjna księdza Bronisława Szymańskiego - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2015)
Rev. Bronislaw Szymański, a Salesian priest, following the indications of the Second Vatican Council, screened religious films in Polish parishes in the years 1965-1988. He was a complete amateur in that area. In the case of foreign films (Italian or English-speaking), it was necessary to translate the texts into Polish. Within 23 years, he presented 11 religious films in over 2.5 thousand projections, which were watched by nearly two million viewers. Those projections were performed mainly in parishes, monasteries and nunneries, seminaries, and for the communities of other faiths. Rev. Szymański was also an experienced and sought-after preacher. In the years 1959-2002 he conducted a 19 one-week retreats for the Salesians and 92 parish retreats for the faithful.